Controversies in orbital reconstruction—III. Biomaterials for orbital reconstruction: a review with clinical recommendations. Issue 1 (January 2016) - Dubois, L.; Steenen, S.A.; Gooris, P.J.J.; Bos, R.R.M.; Becking, A.G.
Abstract: The goal of orbital reconstruction is to repair trauma defects, to correct the position of the eye anatomically, avoiding enophthalmos, and to restore ocular function. For the reconstruction of (trauma) defects, many surgeons recommend materials that can be bent into an anatomical shape and that possess the properties of radiopacity and long-term stability. However, apart from these desired properties, the ideal material for orbital reconstruction remains controversial. Autologous bone is often mentioned as the 'gold standard, ' likely because of its mechanical properties, revascularization potential, and its adaptation to the orbital tissue with minimal acute and chronic immune reactivity. However, autologous bone can show unpredictable resorption rates and suboptimal volume correction. In recent years, an increasing interest in the use of alloplasts for orbital reconstruction has become apparent in the literature. Modern technological advantages, such as preoperative planning, navigation, and perioperative imaging, can be beneficial in the decision to choose a certain implant. The aim of this review is to give a comprehensive overview of the advantages and disadvantages of materials used to reconstruct traumatic orbital defects and to provide a practical, evidence-based, complexity-driven set of guidelines.